International Conference on Ground Anchorages and Anchored Structures in Service 2007 proceedings of the two day international conference organised by the Institution of Civil Engineers and held in London on 26 and 27 November 2007 - Littlejohn, G. S. (Thomas Telford, 2008)
This title shows how routine inspection and monitoring can extend the service life of the anchored structures that represent key elements of a country's infrastructure.
Keywords: Anchorage (Structural engineering) -- Congresses.; elektronické knihy; electronic books